2016
DOI: 10.1039/c5sm02732b
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular polyelectrolyte complex (SPEC): pH dependent phase transition and exploitation of its carrier properties

Abstract: A supramolecular poly-electrolyte complex (SPEC) comprising poly-electrolyte acrylic acid with supramolecularly complexed guanidium is reported. This complex shows pH responsive phase transitions, which are described and characterized using microscopy, spectroscopy, density functional theory studies and Monte Carlo simulations. The phase behaviour of the SPEC is exploited by loading a dye like perylene and a drug, viz., doxorubicin, and their pH dependent controlled release is demonstrated, owing to the pH dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
0
9
0
2
Order By: Relevance
“…Molecular dynamic simulation is a very powerful toolbox in modern molecular modeling, and enables us to follow and understand structures and dynamics with extreme detail‐literally on scales where motion of individual atoms can be tracked . It has been widely used to study the formation mechanism and microstructure of PECHs prepared under different conditions . Molecular dynamics simulation is an effective method to predict the formation process and the microstructure of PECHs prepared by SD‐A‐SGT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamic simulation is a very powerful toolbox in modern molecular modeling, and enables us to follow and understand structures and dynamics with extreme detail‐literally on scales where motion of individual atoms can be tracked . It has been widely used to study the formation mechanism and microstructure of PECHs prepared under different conditions . Molecular dynamics simulation is an effective method to predict the formation process and the microstructure of PECHs prepared by SD‐A‐SGT.…”
Section: Introductionmentioning
confidence: 99%
“…[15] It has been widely used to study the formation mechanism and microstructure of PECHs prepared under different conditions. [16] Molecular dynamics simulation is an effective method to predict the formation process and the microstructure of PECHs prepared by SD-A-SGT. However, because the chain structure of natural polyelectrolyte is influenced by the pH and ion strength of solutions, the flexibility and conformation of polysaccharide vary with the solvent acidity, leading to the cumbersome calculation.…”
mentioning
confidence: 99%
“…Supramolecular self-assembly-driven electrostatic interaction plays a pivotal role in several biological events by creating hierarchical structural features with diverse functionalities. By exploiting supramolecular interaction, it is possible to make a plethora of macromolecular hybrids having distinct bioactive properties along with an enhanced biocompatible feature. , Thus, utilization of supramolecular self-assembly becomes an attractive way to modulate microbial-killing feature. The tuning of bacterial-killing ability by reversible supramolecular assembly–disassembly processes has been recently explored by several groups. , For example, Diacon et al have reported a hybrid sandwich material consists of polymer colloids, silver nanoparticles, and multiwall carbon nanotubes with potential bioactivity .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen bonding is one of the most important factors to consider in the self-assembly of both natural and synthetic macromolecules 1 . However, even a comparatively simple polymer such as poly(acrylic acid) (PAA), a weak polyelectrolyte, experiences a range of other interacting forces (such as hydrophobic and ion-dipole interactions), which affect complex stability and can drive phase transitions [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Complexation with a variety of water soluble polymers were studied. Many of these systems have previously been studied, and besides pH IPC binding can vary depending on bothtemperature, concentration, molar mass and ionic strength [2][3][4][5][6][7][8] . For this study we have measured dilute solutions (0.1-0.5 mg ml -1 ), at low ionic strength at room temperature (18-22 ˚C) to ensure results are comparable.…”
Section: Introductionmentioning
confidence: 99%